2010
DOI: 10.4236/health.2010.27115
|View full text |Cite
|
Sign up to set email alerts
|

Costing of Malaria treatment in a rural district hospital

Abstract: Objective: It is the aim of this paper to estimate the provider's cost of treating paediatric cases of Malaria in a rural African hospital. Furthermore, we intend to give some insights into the possibilities of improving the efficiency of treating children with this disease in order to support policy makers in the resource allocation process. Methods: The cost analysis was done in the district hospital of Nouna, Burkina Faso. Based on a comprehensive cost-of-illness information system, the cost of treating pae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
5
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 28 publications
3
5
0
Order By: Relevance
“…In terms of direct hospital costs, our study showed that medication and hospital stays constitute the highest proportion of costs. This trend also confirms the results of previous studies [22,23,29,30]. The lack of availability of basic medication forces households to buy medicine by themselves in private profit-seeking pharmacies.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In terms of direct hospital costs, our study showed that medication and hospital stays constitute the highest proportion of costs. This trend also confirms the results of previous studies [22,23,29,30]. The lack of availability of basic medication forces households to buy medicine by themselves in private profit-seeking pharmacies.…”
Section: Discussionsupporting
confidence: 91%
“…The estimation of costs allowed for distinction between three groups of households: households paying very expensive costs in private hospitals, households paying intermediate expenditures in state hospitals, and households paying lower expenditures in confessional hospitals. Our results confirm the conclusions of numerous studies carried out in Nigeria, Ethiopia, Sudan, Burkina Faso, and Sri Lanka that found that the medical attention of children suffering from severe malaria in private hospitals was associated with the highest expenditures [16,20,[22][23][24][25]. In this study, the differences in treatment costs observed between public and private hospitals vs. confessional structures confirmed the hypothesis of a lack of adjustment and of under-financing by the Congolese state.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…They suggested keeping price transparency and reliability when prices are increased. According to Stodolak (2008) for hospital prodct pricing zero-base pricing is pricing is best method whereas Koné, Marschall and Flessa (2010) imposed on Activity-based costing method. Moliner (2009) analysed that monetary & non monetary cost has significant impact on patient satisfaction & loyalty towards hospital and according to Cooper (2012) hospital's costs are highly affected with the supply chain practices adopted by the hospitals, so hospital marketer should always try to purchases from manufacturer directly or take advantage of distributor schemes…”
Section: Productmentioning
confidence: 99%